Entrepreneurial characteristics, motives, and business challenges: exploratory study of small- and medium-sized hotel businesses - Ahmad, Syed Zamberi; Muhammad Arif, Afida Mastura (Taylor & Francis, 2016)
The purpose of this study is to gather information about the determinants and characteristics of the owners/managers of small- and medium-sized hotels (SMSHs) and identify various issues in starting up and operating businesses in the United Arab Emirates. The results of this study reveal that the majority of the owners/managers of SMSHs in the United Arab Emirates are male, young and middle age, and relatively new to the tourism industry. The motivations for the business ventures of the entrepreneurs include wanting to be financially independent, become one’s own boss, involvement in family business and the opportunities of the hotel business. Among the key business challenges highlighted by the owners/managers of SMSHs are stiff competition in the hotel industry, increased operating costs, reduced demand, and lack of skilled employees. Several key strategies have been employed to face these challenges. These include offering competitive pricing, improving the marketing and channels of promotion, enhancing the quality of service and providing superior customer service.